Survey Study on Role of Ksheera and Ksheerotpanna Padartha for Longevity - Meena, Anita; Pathan, Ikbal Mohd; Gurjar, Hemwati; Dixit, Mahesh (International Research Journal of Ayurveda & Yoga, 2022)
Ritucharya, Ahar that brings in cumulation ‘swasthya’(Health)to the individual. Ksheer (Milk)is one of the Pranija Aahariya drava dravya enriched with Gunas essential for the efficient smooth functioning of the body. This article is a survey study conducted under Nirogi Rajasthan programe on 1500 people aged above 60 years irrespective of their gender. The data contained in this research was obtained from a study, that consisted of set of questionnaires which reflects on subjective health parameters stated in Ayurveda, achieved after consumption of dairy products. The effect of regular intake of ksheera and ksheerotpanna padarth in context with longevity is explained here. The overall percentage of dugdha Sevana was 84.20%. Same as 1101 person take proper dadhi sevana and overall percentage 73.40% and ghrita sevana 1336 -89.07%. This shows that the people taking Rasayana have better life expectancy (longevity).